2005
DOI: 10.1002/bjs.4975
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognostic significance of lateral lymph node metastasis in patients with advanced low rectal cancer

Abstract: Tumour site, histological type and the presence of mesenteric lymph node metastasis are factors predicting the risk of lateral node metastasis. The poor prognosis of patients with lateral lymph node metastases after systematic lateral dissection suggests the need for adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
155
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(170 citation statements)
references
References 21 publications
14
155
1
Order By: Relevance
“…The incidence of LPLN-positive status (18.3%) in our study was similar to that of pathological LPLN metastasis of previous reports, in which patients underwent surgery alone (1)(2)(3)(4)(5). Following preoperative CRT, 7 of the 19 (36.8%) initially LPLN-positive patients exhibited LPLN downsizing to <7 mm; none of these 7 patients developed recurrence.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The incidence of LPLN-positive status (18.3%) in our study was similar to that of pathological LPLN metastasis of previous reports, in which patients underwent surgery alone (1)(2)(3)(4)(5). Following preoperative CRT, 7 of the 19 (36.8%) initially LPLN-positive patients exhibited LPLN downsizing to <7 mm; none of these 7 patients developed recurrence.…”
Section: Discussionsupporting
confidence: 89%
“…LPLN dissection is often performed with TME in advanced low RC in Japan, as TME does not remove LPLN, which may contain metastasis and lead to local recurrence. The incidence of LPLN metastasis is reportedly 10-20% in patients with advanced low RC who undergo LPLN dissection (1)(2)(3)(4)(5). Although a retrospective analysis has suggested that LPLN dissection is equivalent to preoperative CRT in terms of local control for patients with lower RC (6), the effect of preoperative CRT on patients with involved LPLN has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that local recurrence can be found in 4%-50% of patients with rectal carcinoma after curative resection, and lateral lymph node metastasis may be the important factor for local recurrence [15,16] . Ueno et al [15] reported that patients with lateral node metastases have an increased risk for local recurrence (44% vs 11.7%; P < 0.001) compared with those without lateral node metastases. Sugihara et al [16] also reported that positive lateral lymph nodes are significantly associated with increased local recurrence of rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The survival of patients with advanced low rectal cancer www.wjgnet.com still remains poor. It was reported that lateral lymph node metastasis may be the most important factor for local recurrence and poor prognosis of advanced low rectal cancer [15][16][17][18] . In the current study, the data on 96 consecutive patients who underwent curative surgery with total mesorectal excision and lateral lymph node dissection for advanced low rectal cancer at the Department of General Surgery of Guangdong Provincial People's Hospital were retrospectively analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although the data as well as the attached video were excellent, one important aspect that deserves further comment is discussion regarding combined resection of the iliac vessels.…”
Section: To the Editorsmentioning
confidence: 98%